2017
DOI: 10.1111/jir.12387
|View full text |Cite
|
Sign up to set email alerts
|

Sleep‐disordered breathing and cognitive functioning in preschool children with and without Down syndrome

Abstract: The findings in the TD group support our hypotheses. We recommend that sleep problems are screened for and treated as even mild SDB may prompt poorer cognition and behaviour. For children with DS, we expect that multiple factors in this complex syndrome mask or mediate the association between sleep and cognitive development and tighter controls are necessary to uncover effects of sleep. We propose longitudinal studies as a necessary tool to assess the precise impact of sleep on cognitive development in account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 35 publications
(45 reference statements)
0
31
0
1
Order By: Relevance
“…; Bull & Committee on Genetics ; Chamseddin et al ., ; Esbensen & Hoffman ; Goffinski et al . ; Joyce & Dimitriou ; Kuroda et al . ; Maris et al .…”
Section: Introductionunclassified
See 3 more Smart Citations
“…; Bull & Committee on Genetics ; Chamseddin et al ., ; Esbensen & Hoffman ; Goffinski et al . ; Joyce & Dimitriou ; Kuroda et al . ; Maris et al .…”
Section: Introductionunclassified
“…Sleep is essential for healthy growth and development in children (Joyce & Dimitriou ), as it gives the body a chance to conserve energy, restore its normal processes, promote physical growth and support development (Carter et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high prevalence of sleep disorders during childhood may make children with DS particularly susceptible to ill effects during critical periods of cognitive development. Small cross sectional studies have found deficits in IQ [6], cognitive and behavioural function [74][75][76][77] and accomplishment of daily activities [78] in children with DS and co-existing sleep problems, suggesting an association between poor sleep and these deficits in this group. The age range evaluated in these studies has varied with some groups concentrating on pre-school children with DS [75][76][77] and others examining older children [6,74,78].…”
Section: Potential Impact Of Sleep Disorders In Children With Down Symentioning
confidence: 99%